KEBIJAKAN HILIRISASI SUMBER DAYA ALAM MINERAL DI INDONESIA: ANALISIS BIBLIOMETRIK - Ummah Khoiro, Evada (Jurnal Edueco, 2024)
This research seeks to reveal research trends related to Indonesian government policy in downstreaming natural resources as a contribution of universities to new knowledge and sustainable development. The research method uses literature searches using bibliometric analysis techniques. This data includes 994 articles published in journals indexed by Google Scholar between 2001 and 2024. The data analysis technique utilizes the Harzing's Publish or Perish application and VOSviewer. The research results show that many researchers are discussing policies for the downstreaming of natural resources, especially nickel. Regulation of exports and mining downstream policies have also become topics that have been widely researched in recent years (2023-2024). This is in line with the ban on exports of nickel ore and resources by the Indonesian government, which has received much opposition from world trade organizations such as the European Union.